Penerapan Nilai-Nilai Islam Dalam Sosiologi Pendidikan Di Sekolah - Armiya Nur Lailatul Izzah (https://journal.metanusantara.com/pedagogia, 2025)
The application of Islamic values in the sociology of education in Islamic schools is an important study in an effort to shape the character of students who are not only academically superior but also have high morality. Islamic education does not only focus on cognitive aspects but also on the internalisation of ethical and social values in daily life. This research aims to analyse how Islamic values are implemented in an Islamic school environment and how it affects the social interaction and character building of students. This research uses a qualitative approach with a case study design. Data sources consisted of principals, teachers and students in several Islamic schools selected through purposive sampling technique. Data were collected through in-depth interviews, participatory observation, and document analysis of curriculum and education programmes. Data analysis was conducted using thematic analysis method to identify patterns of Islamic values implementation in Islamic school education. The results showed that the application of Islamic values in Islamic schools is reflected in the integration of Islamic values in the curriculum, character building through social interaction patterns, and extracurricular activities based on Islamic values. The findings confirm that Islamic schools act not only as educational institutions but also as socialisation agents that shape individuals with integrity. However, challenges in integration with the national curriculum as well as limited resources are still the main obstacles. Therefore, a more systematic strategy and support from various parties are needed to increase the effectiveness of the implementation of Islamic values in education.